Report of the Committee on Revision (Document (Virginia. General Assembly), 1849)
1849 Report of the joint Committee of Revision on the reports of the revisors of the Civil Code; having completed the first report, the committee still had to review the remaining ones. The committee estimated that it would need a month and a half longer past that session ending to complete their task and resolved various steps to do so.